The American Society for Clinical Pathology 2020 Vacancy Survey of Medical Laboratories in the United States. Issue 6 (1st December 2021) - Garcia, Edna; Kundu, Iman; Kelly, Melissa; Soles, Ryan
Abstract: Objectives: To determine the extent and distribution of workforce shortages within the nation's medical laboratories. Methods: The survey was conducted through collaboration between the American Society for Clinical Pathology Institute for Science, Technology, and Public Policy in Washington, DC, and the Evaluation, Measurement, and Assessment Department and Board of Certification in Chicago, IL. Data were collected via an internet survey distributed to individuals who were able to report on staffing and certifications for their laboratories. Results: The coronavirus disease 2019 (COVID-19) pandemic disrupted the staffing of clinical laboratories and the stream of incoming graduates entering the workforce. Results show decreased vacancy rates for the majority of laboratory positions across all departments surveyed. The overall anticipated retirement rates continue to decline, which suggests that the field has already lost personnel with vast amounts of experience. Conclusions: Addressing the current and future needs of the laboratory workforce requires a collective effort by numerous groups of stakeholders at all levels, including the laboratory employers, laboratory training programs, health care executives/hospital administrators, and professional organizations. The time is now to address the future shortage of laboratory professionals and to create a resilient clinical laboratory professional workforce.